Performance of a value stock portfolio - Louženský, Filip; Jiroušek, Radim; Bína, Vladislav, 1979-; Vysoká škola ekonomická v Praze. Fakulta managementu (2020)
The purpose of this thesis is to explain the basic principles of value investing and to discover a relationship between fundamental financial ratios and capital return. This study uses multiple sources to determine, whether a portfolio of selected value shares may outperform any main benchmark (DJIA, S&P 500) in the long run. Discussed literature proves the assumption of value portfolio having better results than the market itself to some extent. For this research, I have used data from the US stock market.
Vedoucí práce: Radim Jiroušek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor bakal. práce]; bakalářské práce; bachelor's theses